PENERAPAN SOFTWARE GEOGEBRA DALAM MATERI SEGITIGA DAN SEGIEMPAT UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIK SISWA SMP - Muhamad Diky Fadillah; gagan aditya fauzan; wahyu setiawan (IKIP Siliwangi, 2019)
This study aims to determine the effect of GeoGebra software on junior high school students' mathematical communication skills. The method used is the quasi-experimental method. This research was conducted at Pasundan Rongga Middle School. With class VIII A as an experimental class with 28 students and class VIII C as a control class with 28 students. This study uses instruments that have been tested and declared valid and reliable. The instrument was adjusted to the indicator of mathematical communication skills with the number of questions tested as many as 5 questions to obtain pretest and posttest data in both the experimental class and the control class. Data testing is done using normalized n-gain formula so that the n-gain data obtained is processed using the SPSS 20 application to perform parametric statistical tests. The results showed that the mathematical communication skills of students who learned using GeoGebra software were better than students who learned without using GeoGebra software.